Effects of Pluronic F127 micelles as delivering agents on the vitro dark toxicity and photodynamic therapy activity of carboxy and pyrene substituted porphyrins. (15th September 2018) - Managa, Muthumuni; Britton, Jonathan; Prinsloo, Earl; Nyokong, Tebello
Graphical abstract: The Zn derivatives of 5-(4-carboxyphenoxy)-10, 15, 20-tris(phenyl) and 5, 10, 15, 20-tetra(1-pyrenyl) porphyrins show better photodynamic therapy activity when embedded in Pluronic F127 micelles than their ClGa and metal free derivatives corresponding to the high partition coefficients for the former. Abstract: Metal free, Zn and ClGa containing carboxyphenoxy and phenoxy groups (complexes 1 ) and pyrene groups (complexes 2 ) were synthesized and embedded into Pluronic F127 micelles (represented as F127). Dark toxicity and photodynamic therapy activities of the embedded porphyrins were successfully studied on MCF-7 breast cancer cells. Dark toxicity showed more than 80% cell viability for all complexes. It was found that 1 -Zn + F127 showed better photodynamic therapy activity compared to 1 -H2 + F127, and 1 -ClGa + F127, corresponding to the high partition coefficient for the Zn porphyrin derivatives. The same applies to 2 -Zn + F127 compared to 2 -H2 + F127, 2 -ClGa + F127. 1 -ClGa and 1 -Zn were also linked to Pluronic F127 silica nanoparticles. PDT activities for embedded 1 -ClGa + F127 and 1 -Zn + F127 were much higher than when linked to Pluronic silica nanoparticles (PluS NPs), showing the importance of loading of porphyrins into Pluronic F127 as a drug delivering agent rather than linking. PDT studies at the highest concentration of 60 µg/ml showed decrease in cell viability down to 15.9% for 2 -Zn + F127. The K p was determined in biphasic octanol and water system.